2021
DOI: 10.1021/acsaelm.0c00966
|View full text |Cite
|
Sign up to set email alerts
|

Origin(s) of Anomalous Substrate Conduction in MOVPE-Grown GaN HEMTs on Highly Resistive Silicon

Abstract: The performance of transistors designed specifically for high-frequency applications is critically reliant upon the semiinsulating electrical properties of the substrate. The suspected formation of a conductive path for radio frequency (RF) signals in the highly resistive (HR) silicon substrate itself has been long held responsible for the suboptimal efficiency of as-grown GaN high electron mobility transistors (HEMTs) at higher operating frequencies. Here, we reveal that not one but two discrete channels dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The region of the spatial shift between Al and N was assigned to an intermixed Al-Si-N layer at the AlN/Si interface. 15,34 For sample E, a similar shift was also observed, but with a smaller amplitude of only 0.2 nm, as shown in Figure 3b. It indicates that the formation of the amorphous Al-Si-N interlayer has been effectively suppressed and a sharper AlN/Si heterointerface has been achieved via the USAP approach.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The region of the spatial shift between Al and N was assigned to an intermixed Al-Si-N layer at the AlN/Si interface. 15,34 For sample E, a similar shift was also observed, but with a smaller amplitude of only 0.2 nm, as shown in Figure 3b. It indicates that the formation of the amorphous Al-Si-N interlayer has been effectively suppressed and a sharper AlN/Si heterointerface has been achieved via the USAP approach.…”
Section: Resultssupporting
confidence: 76%
“…25−28 In order to further confirm these results, transmission electron microscopy (TEM) experiments were performed. Panels (a and b) and (c and d) in Figure 1 show the bright-field TEM images under two-beam conditions with g = [0002] and g = [11][12][13][14][15][16][17][18][19][20] for sample A (with conventional pretreatment conditions) and sample E, respectively. It is again shown that both screw-and edge-type threading dislocations in sample E are significantly reduced compared to those in sample A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic of the process flow is indicated in Figure while corresponding experimental results are shown in Figure . Figure a illustrates how the GaN solid immersion lenses are defined and suspended on a strain-optimized heteroepitaxially grown GaN-on-Si chip based on the wafer-scale compatible microfabrication process reported in earlier study . Initially, polymer resist lenses are defined by grayscale lithography and thermal reflow (1), followed by inductively coupled plasma (ICP) dry etching to transfer the lens shape into the 2 μm thick GaN top layer (2).…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…Structure Loss Time Meneghesso G. [29] Si/(AlGa)N/GaN/AlN 0.9 dB/mm @ 10 GHz 2013 Cao L. [30] Si/(AlGa)N/GaN/AlGaN 0.58 dB/mm @ 5 GHz 2017 Cordier Y. [15] Si/(AlGa)N/GaN 0.3 dB/mm @ 10 GHz 2018 Cao L. [20] Si(HR)/(AlGa)N/GaN/AlGaN 0.27 dB/mm @ 20 GHz 2018 Chandrasekar H. [28] GaN-on-Si 0.6 dB/mm @ 6 GHz 2019 Wei L. [11] Si/AlN 1.47 dB/mm @ 6 GHz 2020 Ghosh S. [31] Si/AlN 12.7 dB/mm @ 5 GHz 2021 Si/(AlGa)N/GaN/AlN 0.9 dB/mm @ 10 GHz 2013 Cao L. [30] Si/(AlGa)N/GaN/AlGaN 0.58 dB/mm @ 5 GHz 2017 Cordier Y. [15] Si/(AlGa)N/GaN 0.3 dB/mm @ 10 GHz 2018 Cao L. [20] Si(HR)/(AlGa)N/GaN/AlGaN 0.27 dB/mm @ 20 GHz 2018 Chandrasekar H. [28] GaN-on-Si 0.6 dB/mm @ 6 GHz 2019 Wei L. [11] Si/AlN 1.47 dB/mm @ 6 GHz 2020 Ghosh S. [31] Si/AlN…”
Section: Authormentioning
confidence: 99%